A Perspective of Theory of Reasoned Action and Planned Behavior: Purchase Decision - Roymon Panjaitan; Handy Nur Cahya (Jurnal Manajemen, 2025)
This research addresses the inconsistencies in findings related to celebrity endorsers, brand image, and trust level that influence buying interest to drive purchase decisions for the 3Second brand product. The role of buying interest represents a novel aspect of this study, further explored through the Theory of Planned Behavior (TPB) and the Theory of Reasoned Action (TRA). A quantitative approach involved 100 respondents using the 3Second brand products across Central Java, Indonesia. Data analysis was conducted using SEM-PLS software to develop a structural theory by exploring the relationships between constructs based on TRA and TPB theories. The findings indicate that buying interest significantly contributes, directly and indirectly, to leverage consumer behaviour in making purchase decisions influenced by celebrity endorsers, brand image, and trust level. Additionally, the theoretical implications of TRA and TPB highlight that these theories primarily assume individuals are rational in considering their actions and the implications of those actions.